Palliative care professional's perceptions of barriers and challenges to accessing children's hospice and palliative care services in South East London: A preliminary study. Issue 10 (26th November 2018) - Pentaris, Panagiotis; Papadatou, Danai; Jones, Alice; Hosang, Georgina M.
ABSTRACT: Objectives: Several barriers have been identified as preventing or delaying access to children's palliative care services. The aim of this study is to further explore such barriers from palliative care professionals' perspective from two London boroughs. Methods: Qualitative-five children's palliative care professionals' perceptions were obtained from semi-structured interviews. Results: Three themes emerged: availability and adequacy of child palliative care (e.g., unreliability of services), obstacles to accessing palliative care (e.g., logistical challenges), and cultural values and family priorities. Conclusion: These findings contribute to the equal opportunities dialogue in this sector and the need for future research to address the challenges identified.